The assessment of medical subject mamagers' knowledge on topic of social responsibility = Społeczna odpowiedzialność w zarządzaniu podmiotami leczniczymi - Zadros, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
Over the years the notion of social responsibility in management was only related to economic subjects. Nowadays, a growing number of researchers is of the opinion that in managing subjects which offer social services including medical subjects, we also should implement its rules. However, it seems that in practice the knowledge of managers and employees on that subject is very limited and therefore, it has no reflection is the activities of medical subjects. The author of the article focuses on theoretical and practical aspects of using CSR in managing health care facilities.
Keywords: zarządzanie; CSR; odpowiedzialność społeczna; menedżerowie; podmiot leczniczy; management; Corporate Social Responsibility (CSR); manager; medical subject